Can Vitamin E be a Key Supplementation in Polycystic Ovary Syndrome - Mukundan V, Atheena; Jayakumari, S. (Indian Journal of Pharmacy Practice)
Background: Vitamin E is not a hormone but acts like a hormone (Progesterone). As well as reduce the negative effects of too much androgens. It can also improve insulin sensitivity and inflammation, so remain the most effective treatment strategy for PCOS subjects. This case study describes the effect of Vitamin E supplementation (400 IU/day) on Acne, Hirsutism, menstrual cycle and hormonal levels in a women with PCOS. Materials and Methods: It was a interventional study using Vitamin E Supplementation. Results: Fasting blood samples and BMI were checked before and after 12 weeks of intervention. An eminent relief in acne, hirsutism, menstrual cycle and hormonal levels like follows BMI (28.9 kg/m2 Vs 27.6 kg/m2), FBS (100 mg/dl Vs 92 mg/dl), (4.97IU/L Vs 7.2IU/L), LH (18.03 IU/L Vs 15.21 IU/L), total serum testosterone (130 ng/dl Vs 50 ng/dl). Conclusion: Vitamin E can act as the key supplementation to be add on to the current treatment guideline in improving parameters of PCOS, which will further improve the quality of life in PCOS and also reduce the overall treatment cost, which are generally unaffordable by most individuals with PCOS in India. Key messages: Vitamin E can act as the key supplementation to be add on to the current treatment guideline in improving parameters of PCOS, which will further improve the quality of life in PCOS and also reduce the overall treatment cost, which are generally unaffordable by most individuals with pcos in India.
Keywords: Vitamin E; Polycystic ovary syndrome; LH; FSH; BMI.